Study of the immediate clinical outcome of neonatal sepsis in the neonatal I.C.U. of a tertiary care hospital - Reshad, Mohamed; Mundol, Tania; K., Mithun H.; Prabhu, Anitha S. (International Journal of Contemporary Pediatrics, 2017)
Background: According to the status of newborns report 2014, about 0.76 million neonatal deaths occur in India, the highest for any country in the world. Although the neonatal mortality rate (NMR) has declined in the last 2 decades, the early NMR has been the slowest to decline. The three major causes of neonatal deaths are preterm birth complications, infections, and intrapartum related complications; together, they contribute to nearly 90% of total neonatal deaths. The aim of the study was to study the immediate clinical outcomes of culture proven neonatal sepsis in the NICU of Yenepoya Medical College Hospital during the period January 2016 to June 2016. Methods: Retrospective hospital based study of records of all neonates admitted to the NICU with blood culture positive neonatal sepsis from January 2016 till June 2016. Blood cultures were done using the BACTEC 460. Data analysed using SPSS version 20. Results: A diagnosis of probable sepsis was made in 84 (54%) of the total neonates (154) admitted to the NICU during the study period of which 6 were out born babies. Culture positive sepsis was found in 11.6% (18). The most commonly isolated organisms were Escherichia coli, Enterococcus and coagulase negative Staphylococcus aureus. Of the total 18 culture positive cases, urine culture was positive in only 2 cases while the remaining had a positive blood culture. Among the 18 cases of culture positive neonatal sepsis, 8 died while 10 survived. Conclusions: Incidence of neonatal sepsis was relatively high in YMCH with the most predominant organism being coagulase negative Staphylococcus aureus. 12.7% of the sepsis cases died. Resistance to cefotaxime and ampicillin was prevalent.